Choosing Wisely India: ten low-value or harmful practices that should be avoided in cancer care. Issue 4 (April 2019) - Pramesh, C S; Chaturvedi, Harit; Reddy, Vijay Anand; Saikia, Tapan; Ghoshal, Sushmita; Pandit, Mrinalini; Babu, K Govind; Ganpathy, K V; Savant, Dhairyasheel; Mitera, Gunita; Sullivan, Richard; Booth, Christopher M; et al.
Summary: The Choosing Wisely India campaign was an initiative that was established to identify low-value or potentially harmful practices that are relevant to the Indian cancer health-care system. We undertook a multidisciplinary framework-driven consensus process to identify a list of low-value or harmful cancer practices that are frequently undertaken in India. A task force convened by the National Cancer Grid of India included Indian representatives from surgical, medical, and radiation oncology. Each specialty had representation from the private and public sectors. The task force included two representatives from national patient and patient advocacy groups. Of the ten practices that were identified, four are completely new recommendations, and six are revisions or adaptations from previous Choosing Wisely USA and Canada lists. Recommendations in the final list pertain to diagnosis and treatment (five practices), palliative care (two practices), imaging (two practices), and system-level delivery of care (two practices). Implementation of this list and reporting of concordance with its recommendations will facilitate the delivery of high-quality, value-based cancer care in India.